Supercontinuum generation in nonlinear optical fibers with higher order nonlinearity - Umarov, Bakhram; Hassan, Torla (2011)
We present a results of the modelling of supercontinuum generation in highly nonlinear photonic crystal fibers (PCFs) with picosecond pulses. We focused on the theoretical study of the soliton radiation in the optical systems with non-Kerr nonlinearities. The problem can be modeled by nonlinear Schrödinger (NLS) equation with higher order perturbations. Physical systems to which the model pertains includes optical fibers and waveguides fabricated from materials with high nonlinearities. We have found numerically a soliton solution of NLS equations with cubic-quintic and saturated nonlinearity. Then we have investigated the Cherenkov radiation in these systems. The connection between a solitons radiation and a supercontinuum generation in nonlinear optical systems is discussed.